IMPARTIALITY PRINCIPLE: MENILIK PRINSIP KETIDAKBERPIHAKAN HAKIM MAHKAMAH KONSTITUSI DALAM KASUS ANWAR USMAN - Rayhan, Alendra Nauval Mufti (CENDERAWASIH CONSTITUTIONAL REVIEW, 2026)
The Constitutional Court serves as the Guardian of the Constitution, safeguarding the interests of the people and ensuring a system of checks and balances in accordance with constitutional mandates. In its capacity as the Guardian of the Constitution, the Court is required to uphold the highest standards of integrity and morality. Consequently, a professional code of ethics was established as a formal mechanism to enforce ethical conduct and preserve the integrity of constitutional justices. In practice, however, ethical violations by constitutional justices persist. On March 28, 2024, Constitutional Justice Anwar Usman was found to have committed a breach of the Code of Ethics and Conduct for Constitutional Justices; as a sanction, he was removed from his position as Chief Justice of the Constitutional Court. This research aims to analyze the chronology and the specific principles violated by Anwar Usman, and to examine the proper application of the principle of impartiality, which serves as the central issue in the Anwar Usman case. Utilizing a normative legal research method through a conceptual approach integrated with a statute approach, this study concludes: First, Anwar Usman committed an ethical breach by participating in a Constitutional Court decision that benefited his nephew, Gibran Rakabuming Raka, facilitating his candidacy for Vice President. This violation encompassed five principles of the code of ethics, including impartiality, integrity, and independence. Second, the implementation of the principle of impartiality consists of five specific applications as stipulated in the Regulation of the Constitutional Court of the Republic of Indonesia Number 09/PMK/2006 concerning the Enforcement of the Declaration of the Code of Ethics and Conduct for Constitutional Justices.